Tim Virtual dan Faktor-Faktor yang Mempengaruhi Efektivitas Kerjasama dalam Tim Virtual - Mulyani Mulyani (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2016)
Nowadays, a Virtual Team has growing rapidly and become one of a trend model in business activities; it’s growing is in compliance with technology advance in the world without any boundaries concept. A virtual team has its member around the world, communicate each other using media technology, and almost never meet up at all. As a traditional (conservative) team, a Virtual Team also influenced by many factors to determine its effectiveness. Base on literature research, Reseacher found several factors which is influence to Virtual Teams effectiveness, such as trust, communication and depth of relationship, goal & share understanding, commitment, leadership, technology and trainings. Keyword: Virtual Team, Tradisional Team, Team collaboration, Team Effectivevities